Consumer Decision-Making Abilities and Long-Term Care Insurance Purchase. (25th May 2017) - McGarry, Brian E; Tempkin-Greener, Helena; Grabowski, David C; Chapman, Benjamin P; Li, Yue
Abstract: Objectives: To determine the impact of consumer decision-making abilities on making a long-term care insurance (LTCi) purchasing decision that is consistent with normative economic predictions regarding policy ownership. Method: Using data from the Health and Retirement Study, multivariate analyses are implemented to estimate the effect of decision-making ability factors on owning LTCi. Stratified multivariate analyses are used to examine the effect of decision-making abilities on the likelihood of adhering to economic predictions of LTCi ownership. Results: In the full sample, better cognitive capacity was found to significantly increase the odds of ownership. When the sample was stratified based on expected LTCi ownership status, cognitive capacity was positively associated with ownership among those predicted to own and negatively associated with ownership among those predicted not to own who could likely afford a policy. Discussion: Consumer decision-making abilities, specifically cognitive capacity, are an important determinant of LTCi decision outcomes. Deficits in this ability may prevent individuals from successfully preparing for future long-term care expenses. Policy makers should consider changes that reduce the cognitive burden of this choice, including the standardization of the LTCi market, the provision of consumer decision aids, and alternatives to voluntary and private insuring mechanisms.